Different effect of hypercholesterolemia on mortality in hemodialysis patients based on coronary artery disease or myocardial infarction. Issue 1 (December 2016) - Lin, Yi-Chun; Lin, Yen-Chung; Chen, Hsi-Hsien; Chen, Tzen-Wen; Hsu, Chih-Cheng; Peng, Chiung-Chi; Wu, Mai-Szu
Abstract Background Studies on the association of total cholesterol (TC) levels and mortality in hemodialysis (HD) patients demonstrated conflicting results. The differenct effect of Hypercholesterolemia on HD patients based on the presence of myocardial infarction (MI) or coronary artery disease (CAD) is unknown. Methods We analyzed data from the Taiwan Renal Registry Data System (TWRDS) between 2005 and 2012. Patients were divided into MI/CAD or non-MI/CAD group. The primary outcome was three-year mortality. The association between primary outcome and first year average TC and effect of change in cholesterol level between the first and third year of dialysis were explored. Results Of 90, 795 HD patients, 77, 762 (85.6%) patients were assigned to non-MI/CAD group and 13, 033 (14.4%) to the MI/CAD group. In the non-MI/CAD subjects, both TC > 250 mg/dL and < 150 mg/dL were associated with increased risk of mortality (adjusted hazard ratio [HR]; 95% confidence interval [CI]: 1.27; 1.17–1.37 and 1.14; 1.11–1.18) compared to the reference (TC: 150–200 mg/dL). In the MI/CAD patients, only TC < 150 mg/dL had increased risk (HR; 95% CI: 1.15; 1.08–1.24). In addition, patients of the non-MI/CAD group with highest level of TC (>250 mg/dL) in both first and third year of dialysis had a 64% increased risk for mortality (HR: 1.64, 95% CI: 1.51–1.80). Conclusion In this nationwide hemodialysis cohort, hypercholesterolemia was associated with increased mortality in HD patients without MI/CAD. Further investigation on primary prevention of CAD with statin is warranted.